Characterizing Block Graphs in Terms of One-vertex Extensions - Markenzon, Lilian; Waga, Christina Fraga Esteves Maciel (Trends in Computational and Applied Mathematics, 2019)
Block graphs has been extensively studied for many decades. In this paper we present a new characterization of the class in terms of one-vertex extensions. To this purpose, a specific representation based on the concept of boundary cliques is presented, bringing about some properties of the graph.